Investment style of Jordanian mutual funds - Ishaq Hacini; Khadra Dahou; Mohamed Benbouziane (International Journal of Economic Sciences and Applied Research, 2012)
The study investigates the mutual funds investment style in the Jordanian context. It uses monthly returns of five mutual funds from July 2000 to December 2009. To do so, it employs the 4-factors model with explanatory variables the market portfolio return, a small minus large capitalization indicator variable, a high minus low book-to-market indicator variable, and a variable that account for momentum effect. These factors are used as benchmarks to investigate the investment style. The results indicate that mutual funds returns tend to follow those of the market portfolio. In terms of investment style, mutual funds managers tend to favor small capitalization stocks, past winners stocks, and low book-to-market ratio stocks, respectively.
Keywords: C33; G11; G23; 330; mutual funds; 4-factors model; investment style; market portfolio; size; book-to-market; momentum; Investmentfonds; Kapitalanlage; Portfolio-Management; Kapitalertrag; Jordanien